Pengaruh motivasi belajar terhadap hasil belajar di SD Negeri Sanggrahan 2 - Nia tarmiyati (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of learning motivation on student learningoutcomes at SD Negeri Sanggrahan 2 for the academic year 2020/2021. Motivation iseverything that can affect success in learning activities. Learning will be difficult to reachan optimal point without motivation. This study uses a descriptive correlation which iscarried out to study the problems of fourth grade elementary school students in knowinghow much the level of motivation influences student learning outcomes in elementaryschool in grade IV SD Negeri Sanggrahan 2 as a sample in this research. In collectingdata, it can be done by using an instrument questionnaire of the motivation variable andstudent test results as the average variable for the achievement of student success. thedata processing is done by calculating the statistics and the average correlation. The datashows an explanation of the high level of reliability and the magnitude of the influenceof learning motivation on learning outcomes where calculated = 3.26 and table = 1.73,with a significant level of 0.05 meaning Ha is accepted and Ho is rejected, and so theconclusion is that there is an effect of motivational outcomes on learning outcomes inelementary school.